IMPLEMENTASI METODE PEMBELAJARAN MIND MAPPING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS NEGERI 1 MALANG - Hanif, Ahmad Fachruddin (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
In carrying out teaching and learning activities, teachers and students are the most important components in it. It can be said that the teacher is a facilitator who guides students to achieve the desired learning goals. In learning, one of which is the History of Islamic Culture, teachers often encounter many obstacles, mainly on student motivation and learning outcomes. In this case, the purpose of the study was to determine the improvement of both through the mind mapping method applied at MTs Negeri 1 Malang with the research subjects being class VIII F and VIII I, totaling 33 students and 32 students. This research is a classroom action research using a qualitative approach with data collection through documentation and tests. The research was also conducted in two cycles, each cycle covering planning, action, observation, and reflection. The results of the second class pre-cycle research showed 30% completeness results. Then in the first cycle the percentage of students' completeness was 74% for class VIII F and 100% for class VIII F. Furthermore, for the second cycle class VIII I showed a percentage of 77% and class VIII I showed a percentage of 62,5% so it can be concluded that the jigsaw method is very effective in improving learning outcomes. students in the subject of Islamic Cultural History at MTs Negeri 1 Malang. In addition, in applying the mind mapping method there are two factors that influence it, namely the first factor is the supporting factor such as students are more enthusiastic about mastering the material, students are easy to accept and understand the material, and the teacher gets some new innovations in developing learning. While the second factor is the inhibiting factor, such as the uncontrollability of students when the group division takes place and the presence of students who tend to be unenthusiastic about undergoing this activity because they feel that there are several members of their group who are able to complete the task. Abstrak Dalam melaksanakan kegiatan belajar mengajar, guru dan siswa adalah komponen terpenting yang ada di dalamnya. Bisa dikatakan guru sebagai fasilitator yang membimbing siswa untuk mencapai tujuan pembelajaran yang diinginkan. Dalam pembelajaran salah satunya Sejarah Kebudayaan Islam, seringkali guru menemui banyak hambatan utamanya pada motivasi dan hasil belajar siswa. Dalam hal ini, tujuan penelitian adalah untuk mengetahui peningkatan keduanya melalui metode pembelajaran mind mapping yang diterapkan di MTs Negeri 1 Malang dengan subjek penelitiannya kelas VIII F dan VIII I yang berjumlah 33 siswa dan 32 siswa. Penelitian ini merupakan penelitian tindakan kelas menggunakan pendekatan kualitatif dengan pengumpulan data melalui dokumentasi dan tes. Penelitian juga dilakukan dengan dua siklus, yang setiap siklusnya mencangkup perencanaan, tindakan, observasi, dan refleksi. Hasil penelitian pra siklus kedua kelas menunjukkan hasil ketuntasan 30%. Kemudian siklus pertama prosentasi ketuntasan siswa sebanyak 74% untuk kelas VIII F dan 100% untuk kelas VIII F. Selanjutnya untuk siklus kedua kelas VIII I menunjukkan prosentase 77% dan kelas VIII I menunjukkan prosentase 62,5% sehingga bisa disimpulkan metode pembelajaran mind mapping sangat efektif meningkatkan hasil belajar siswa dalam mata pelajaran Sejarah Kebudayaan Islam di MTs Negeri 1 Malang. Selain itu dalam menerapkan metode pembelajaran mind mapping ada dua faktor yang mempengaruhinya, yakni faktor pertama adalah faktor pendukung seperti siswa lebih bersemangat menguasai materi, siswa mudah menerima dan memahami materi, serta guru mendapatkan beberapa inovasi baru dalam mengembangkan pembelajaran. Sedangkan faktor kedua adalah faktor penghambatnya, seperti tidak terkendalinya siswa ketika pembagian kelompok berlangsung dan adanya siswa yang cenderung tidak antusias menjalani kegiatan ini karena merasa ada beberapa anggota kelompoknya yang mampu menyelesaikan tugas